2020
DOI: 10.1371/journal.pone.0241616
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density and trabecular bone score in elderly type 2 diabetes Southeast Asian patients with severe osteoporotic hip fractures

Abstract: Introduction Studies show trabecular bone score (TBS) may provide information regarding bone quality independent of bone mineral density (BMD) in type 2 diabetes (DM2) patients. We analyzed our Southeast Asian severe osteoporotic hip fracture patients to study these differences. Methods We conducted a retrospective cross-sectional analysis of subjects admitted to Changi General Hospital, Singapore with severe osteoporotic hip fractures from 2014–2017 who had BMD performed. Electronic records were reviewed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…For male patients, only a 'possible' trend is noted that East Asian patients measure lower total hip T-scores. Another point noted is that, around the timepoint of a hip fracture, at least for East Asians included in this study, male patients tend to measure higher femoral neck and total hip T-scores than those of female patients (Figure 4) (24,28,29,30,32,33). .…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…For male patients, only a 'possible' trend is noted that East Asian patients measure lower total hip T-scores. Another point noted is that, around the timepoint of a hip fracture, at least for East Asians included in this study, male patients tend to measure higher femoral neck and total hip T-scores than those of female patients (Figure 4) (24,28,29,30,32,33). .…”
mentioning
confidence: 76%
“…For the data in the articles included for analysis, the results are shown in Figure 1 for female patients (24)(25)(26)(27)(28)(29)(30)(31)(32)(33), Figure 2 for male and female patients mixed (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45), and Figure 3 for male patients (24,(28)(29)(30)32,33,46,47). For the data in Figure 2, females commonly constituted 2/3 of the cases, reflecting that hip fracture prevalence among older women is about double of that among older men.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is evidence showing higher TBS values among T2DM patients than controls [ 20 ] as well as evidence showing no significant difference in this regard, despite significant higher values of BMD among diabetics, for example, a case-control study by Zhukouskaya et al on 99 diabetic patients and 107 controls showing that TBS values were not significantly different among DM patients and controls; however, it was lower in patients with DM who suffered fractures [ 21 ]. Another population-based study among the Iranian population consisting of 2263 participants aged 60 years and above also showed that mean TBS values were not significantly different among diabetics and normoglycemics [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the fewer the number of remaining teeth, the lower the masticatory function; hence, the results of this study can be considered consistent [ 37 ]. These results suggest that the target population of this study can be representative of the general population with a common pathology, considering tooth loss due to periodontal disease and the association between diabetes and periodontal disease and between diabetes and bone mineral density [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%